The Mediating Role of Depression Severity on the Relationship Between Suicidal Ideation and Self-Injury in Adolescents With Major Depressive Disorder - Kang, Byungjoo; Hwang, Jaeuk; Woo, Sung-il; Hahn, Sang-Woo; Kim, Minjae; Kim, Younggeun; Jin, Hyeonseo; Jeon, Hong Jun; Lee, Yeon Jung (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2022)
Objectives: Suicide is the leading cause of death among adolescents in South Korea, and depression and personality profiles have been identified as significant risk factors for self-injurious behavior. This study examined the influence of depressive mood and temperament/ character on self-injury in adolescents.Methods: A total of 116 adolescents (aged 12–18 years) with a primary diagnosis of major depressive disorder (MDD) and their parents were enrolled in this study. The participants were divided into three groups based on adolescent’s self-injury frequency, and their Children’s Depression Inventory (CDI), Youth Self-Report (YSR), and Temperament and Character Inventory (TCI) scores were compared. Finally, mediation analysis was conducted to investigate the relationship between suicidal ideation and self-injury.Results: Of study participants, 75.9% answered that they had suicidal ideation, and 55.2% answered that they had engaged in self-injurious behavior in the last six months. There were significant differences in CDI and suicidal ideation among the groups. After adjusting for age and sex, mediation analysis indicated that depressive mood mediated the relationship between suicidal ideation and self-injury.Conclusion: This study emphasizes the importance of evaluating and managing depressive mood severity in adolescents with MDD as these factors partially mediate the transition from suicidal ideation to self-injury.